CXCR4-targeted therapy in lung cancer: plerixafor as a promising antimetastatic agent - Ramalingam, Prasanna Srinivasan; Afzal, Muhammad; Babu, M. Arockia; Rekha, Manjunath Mirle; Sahoo, Samir; Pandey, Surya Nath; Goyal, Kavita; Hussain, Md Sadique; Gupta, Gaurav; Balakrishnan, Purushothaman; Arumugam, Sivakumar (Frontiers in Pharmacology, 2025)
Metastasis remains the prime cause of poor prognosis in lung cancer, a leading cause of cancer-related mortality worldwide. Because CXCR4/CXCL12 constitutes a powerful therapeutic target to counter tumor progression, immune evasion, and therapy resistance, it plays a pivotal role in lung cancer. Expression of CXCR4 is high in non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) and has been correlated with aggressive tumor behavior increased metastatic spread to the bone marrow, the liver, and the brain, and poor overall survival. Studies in preclinical models have demonstrated that plerixafor is a CXCR4 inhibitor that can reduce tumor cell migration, increase chemosensitivity, and re-establish immune response to limit metastasis and increase treatment efficacy. Furthermore, clinical trials combining plerixafor with chemotherapy as well as immune checkpoint inhibitors in NSCLC patients demonstrate that this drug increases T cell infiltration, increases the ability of the tumor to stimulate anti-tumor immunity, and increases progression-free survival. However, although there are promising preclinical and encouraging early clinical data, it is important to address several issues before CXCR4-targeted therapies can become an integral part of lung cancer treatment. They include tumor heterogeneity, adaptive resistance mechanisms, as well as the complexity in the tumor microenvironment of CXCR4 signaling. Additionally, drug development strategies aimed at suppressing CXCR4-driven immune suppression and radioresistance must be combined with chemotherapy, radiotherapy, and immunotherapy therapies to maximize therapeutic benefits. Imaging of CXCR4 with specific PET and the selection of patients on CXCR4 biomarker criteria offer the possibility of further improving precision medicine approaches so that CXCR4-targeted therapies will only be given to the most CXCR4-responsive patients. The role of CXCR4 in lung cancer pathogenesis and development is critically reviewed, the most recent results on plerixafor inhibition of CXCR4 are summarized, and new, potential strategies for combination treatment of CXCR4 with other inhibitors are explored.